IMPLEMENTATION OF THE KEMP MODEL IN THE SUBJECT OF ISLAMIC RELIGIOUS EDUCATION AND CHARACTER AT SMP IT BAITUL ILMI CIANJUR - Meliana, Siska; Ruswandi, Uus; Yudi, Yudi; Fauzi, Rai Ahmad (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
This paper aims to describe the implementation of the Kemp model in PAdBP subjects at Baitul Ilmi Cianjur IT Junior High School. The method used is descriptive qualitative which is analyzed using four important elements of the Kemp model including problem identification, learning objectives, methods and evaluation. Based on the findings, the implementation of the Kemp Model in the planning stage is: RPE, annual program, semester program, syllabus, and lesson plan (RPP). In the implementation stage of the Kemp Model implementation, teachers identify learner information and student characters, determine learning objectives, determine learning methods and conduct evaluations. The evaluation stage of implementation with the Kemp Model uses written tests, memorization tests, PTS and PAS as assessment instruments. Through the stages of the Kemp Model, learning becomes more effective and efficient, making it easier for teachers to design learning